Mycobiota in chilli Capsicum annuum and Chilean merkén - Costa, Jéssica (2019)
Berry fruits of Capsicum annuumcv. "Cacho de Cabra” are used for the manufacture of a traditional pepper powder known as Merkén, which is a Chilean spicy powder with smoky flavour produced through both industrial and artesian processes. Merkén contamination with Ochratoxin A (OTA) is a main concerning for industries and local producers. Therefore, the main goal of this study was to search for the cultivable mycobiota on the whole processing stages of chilli used in traditional Merkén production. Capsicum annuum samples were provided by 8 farmers from 4 localities of the Chilean Region of La Araucanía. Chilli berry fruits were collected at five different sampling time points of production: (I) just at the day of ripe fruits harvest; (II) after 30 days of harvest (drying process); (III) during the smoking process; (IV) ingredients added to Méken (e.g., coriander seeds) and (V) Merkén samples from local markets. Samples were used for isolation of cultivable mycobiota on MEA, DRBC and DG18 media. Isolated fungal strains were identified using classical morphology, MALDI-TOF MS and molecular biology. A total of 225 fungal strains belonging to 9 fungal genera were identified. From the sampling point I, 61 fungal strains were isolated. From these, strains were distributed among Penicillium spp. (25), Fusarium spp. (14), Alternaria spp. (9), Aspergillus spp. (7) and others (6). From the sampling point II, 46 fungal strains were isolated. These strains were distributed among: Penicillium spp. (24), Aspergillus spp. (12), Alternaria spp. (7) and other species (3). From the sampling point III, 85 fungal strains were identified. These strains were distributed among: Penicillium spp. (63), Aspergillus spp. (18), and other species (4). From the sampling point IV, were isolated only Penicillium spp. (6), Aspergillus spp. (4). While, from sampling point V, the isolated strains were Penicillium (10), Aspergillus (4), Fusarium (1), and other (8). This study demonstrates that Merkén production process is increasingly selective for occurrence of Aspergillus and Penicilliumspecies, which already emerge in the early stages of the Capsicum production. In addition, Alternaria and Fusariumwere also present in C. annuum, mainly in fresh fruits. The evaluation of OTA production by the potential OTA producers fungal species isolated in the whole Merkén production/commercialisation chain is now under course